A three-year study of nosocomial infections associated with Pseudomonas aeruginosa. - Sherertz, R J (1983)
During a 3-year study period in a university teaching hospital, 417 nosocomial infections associated with Pseudomonas aeruginosa were documented in 321 patients. The overall rate of P. aeruginosa nosocomial infection was 5.3 cases per 1,000 patients. Residence on the surgery or medicine service, advanced patient age, and exposure to the burn, surgery, or medicine intensive care units correlated with higher rates of infection. The most common sites for P. aeruginosa infection were the lower respiratory tract, urinary tract, blood stream, and surgical wounds. Nosocomial P. aeruginosa lower respiratory tract and blood stream infections were significantly associated with exposure to certain intensive care units, whereas P. aeruginosa urinary tract infections more commonly occurred on the neurology and neurosurgery services. Results of live antigen serotyping showed that serotype 6 was most common, followed by serotypes 1 and 11. Serotype 6 correlated with resistance to carbenicillin, gentamicin, and tobramycin, and serotype 11 correlated with resistance to carbenicillin. Two-thirds of the isolates tested were sensitive to carbenicillin, gentamicin, and tobramycin, but 13.2% were resistant to all three of these drugs. P. aeruginosa isolates resistant to all three drugs were associated with urinary tract infections.